Gum arabic as a sole wall material for constructing nanoparticle to enhance the stability and bioavailability of curcumin - Chao Ai; Chengang Zhao; Chunhong Xiang; Yimei Zheng; Saiyi Zhong; Hui Teng; Lei Chen (Food Chemistry: X, 2023)
In this study, a kind of nanoparticle prepared using gum arabic as a sole wall material for loading curcumin was obtained. The properties and digestive characteristics of the curcumin-loaded nanoparticle were determined. Results showed that the maximum loading amount of the nanoparticle was 0.51 µg/mg with an approximately 500 nm size. The Fourier transform infrared (FTIR) spectrum showed that the complexation was mainly related to the -CO, –CH, and -COC- groups. The curcumin-loaded nanoparticle exhibited good stability under highly concentrated salinity stress, and the stability of the curcumin loaded in nanoparticles was significantly higher than that of free curcumin under ultraviolet radiation. The curcumin loaded in nanoparticle was released mainly in the intestinal digestion stage, and the release process was sensitive to the pH changes rather than protease. In conclusion, these nanoparticles can be a potential nanocarrier for enhancing the stability of curcumin which can be applied in the salt-containing food system.